Kinetics and thermodynamic modelling for CO2 capture using NiO supported activated carbon by temperature swing adsorption - Lahuri, Azizul Hakim; Mohd Yusuf, Athirah; Adnan, Rohana; Abdul Rahim, Afidah; Tajudeen, Nur Farah Waheed; Nordin, Norazzizi (Biointerface Research in Applied Chemistry, 2021)
Abstract: Solid sorbent from functionalized activated carbon (AC) could enhance the adsorption capacity in CO2 capture. This study emphasizes cyclic CO2 capture using NiO functionalized AC. Different loadings of NiO impregnated on AC were synthesized. This work showed that the most efficient adsorbent of 0.05NiO/AC exhibits an adsorption capacity of 55.464 mg/g at the adsorption temperature of 30 °C by using the temperature swing adsorption method. A slight loss of adsorption capacity at 0.28 % for a five cycles CO2 capture indicated consistency potential for large scales application. The adsorbent exhibited a slightly lower surface area compared to AC, but the presence of NiO improved the adsorption capacity by chemisorption phenomena. The NiO acts as the basic site for CO2 capture. Meanwhile, AC as support could increase the surface area of active sites and reduce the sintering effect of the NiO. It was found that various adsorption temperatures had a good correlation with the pseudo-second-order kinetic model. The magnitude of the sorption process was evaluated by the activation energy of 48.09 kJ/mol, which implies a chemisorption process at various adsorption temperatures. Thermodynamic studies explained the CO2 adsorption process for this study was found to be a spontaneous and endothermic process.